(untitled) (Journal of Environmental Science and Natural Resources, 2015)
This study assessed the extent and trend of landuse/cover change in three selected area of Dhaka city, Bangladesh. This paper examined the use of GIS and Remote Sensing in mapping Land Use/Land Cover in Dhaka city of Landsat imageries of 1960, 2000 and 2014 were downloaded from the Landsat website and to detect the changes that has taken place in this status between these periods. Remote sensing and GIS based software (ILWIS) were used to produce and analysis the land use maps and least square method was functioned to identify the trend of land use change in the study areas. The images were analyzed using unsupervised classification approach in ILWIS 4.1 environment. The present study expressed the experiences of unplanned land use change in Dhaka city. And it is found that the study area follows the pattern of urbanization without planned development. Consequently, the pattern of unplanned land use change in Dhaka city will make it a haphazard city in World. DOI: http://dx.doi.org/10.3329/jesnr.v7i2.22217 J. Environ. Sci. & Natural Resources, 7(2): 105-109 2014